Structural Properties of Nano (CdO) Semiconduction Thin Film Deposited by Spray Pyrolysis Technique - Bukheet Hasan, Nahida; Ahmed Mohammed, Mohammed (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper CdO films of 160 nm thickness were deposited onto glass substrates by spray pyrolysis technique at 400 oC temperature. The structure of films where studied , X-ray measurements showed that the polycrystalline film and have a grain size of 14.63 nm. As shown images of atomic force microscope that the film surface roughness of 3.26 nm .The photo of scanning electron microscope show that the film and free from cracks and holes have a superficial homogeneity. The energy-dispersive X-ray analysis show that the film containing the pure and elemental cadmium and oxygen only signifying purity film prepared.